2001
DOI: 10.7589/0090-3558-37.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Hematological, Protein Electrophoresis and Cholinesterase Values of Free-Living Nestling Peregrine Falcons in Spain

Abstract: Protein electrophoresis, hematological and cholinesterase values were determined in 32 nestling free-living peregrine falcons (Falco peregrinus) (15- to 27-days-old) in order to establish normal reference values for this population. The following values (mean +/- SD) were observed: prealbumin 0.31 +/- 0.04 g/dl, albumin 1.25 +/- 0.06 g/dl, alpha1 and alpha2-globulin 0.23 +/- 0.02 and 0.16 +/- 0.02 g/dl respectively, beta-globulin 1.02 +/- 0.05 g/dl, gamma-globulin 0.060 +/- 0.08 g/dl, total protein 3.79 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 20 publications
2
5
2
Order By: Relevance
“…The α 1 -globulin fraction is often not detectable in plasma of healthy birds from most avian species, while plasma from raptorial species show a high-amplitude fraction branching off the albumin spike [44]. The mean concentration of α 1 -globulin in the present study was 2.4% of the total protein content (Additional file 1: Table S2), which is lower than what has been found for α 1 -globulins in peregrine falcon nestlings (6.4% of the total protein content, [29]). The concentrations of the present study were close to 1.4 g/L or 4% of total protein as found in plasma of adult bald eagles using AGE [24].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The α 1 -globulin fraction is often not detectable in plasma of healthy birds from most avian species, while plasma from raptorial species show a high-amplitude fraction branching off the albumin spike [44]. The mean concentration of α 1 -globulin in the present study was 2.4% of the total protein content (Additional file 1: Table S2), which is lower than what has been found for α 1 -globulins in peregrine falcon nestlings (6.4% of the total protein content, [29]). The concentrations of the present study were close to 1.4 g/L or 4% of total protein as found in plasma of adult bald eagles using AGE [24].…”
Section: Discussioncontrasting
confidence: 53%
“…The electrophoretic patterns found for the white-tailed eagle nestlings in the present study resembled those found for black kite ( Milvus migrans ) by CE analyses [38] and bald eagle ( Haliaeetus leucocephalus ) nestlings by AGE analyses [41]. The concentrations of total protein, albumin, α 2 -, β- and γ-globulins were also similar to those observed by AGE of plasma from healthy stellar’s sea eagle ( Haliaeetus pelagicus ) and bald eagle adults [41], and within the range of concentrations observed in free-living nestling peregrine falcons ( Falco peregrinus ) by cellulose acetate electrophoresis [29]. Compared to these previous studies, the most notable differences were the lower levels of α 1 -globulin and higher levels of prealbumin in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, the fact that the number of erythrocytes is low or normal can be defined as MCV anemia. The MCV, MCH and MCHC levels of hemoglobin and hematocrit that were detected in this study are found to be similar to the values declared in previous studies (Smith & Bush 1978;Lanzarot et al 2001 (Shen et al 2008), as determined by various researchers. Also, the diameter of the erythrocyte is 12.60 × 9.80 µm and the diameter of the nucleus is 12.60 × 9.80 µm in eagles; the diameter of the erythrocyte is 16.50 × 6.50 µm and the diameter of the nucleus is 7.50 × 2.00 µm in vultures (Polo et al 1992); and the diameter of the erythrocyte is 27.30 × 13.00 µm and the diameter of the nucleus is 7.20 × 3.30 µm in kestrels (Shen et al 2008).…”
Section: Parameterssupporting
confidence: 77%
“…It is thought that the possible reason for this is that Sparrowhawks have protozoal or parasitary disease in their blood or gastrointestinal system. Also, many researchers (Kirkpatrick & Lauer 1985;Barnard & Bair 1986;Peirce et al 1990;Lanzarot et al 2001) frequently state that there might be hematozoon or gastrointestinal parasites in the blood of wild birds like Sparrowhawks. On the other hand, our parasitological examination did not find any types of blood parasite infection or gastrointestinal parasites.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation